Odpowiedź :
a) -5*3a-5b-5-(-2c) = -15a -5b+10c
b) 2x-6y-3x+3y-20x-15y= -21x -18y
c) 4*6x-4*8-2x*6x-2x*(-8)= 24x-32-12x(do kwadratu)+16x= 40x-32-12x(do kwadratu)= 12x(do kwadratu)+40x-32
d) 4x*(-2x(do kwadratu)-3x+1)+3*(-2x(do kwadratu)-3x+1)= -8x(do sześcianu) - 12x(do kwadratu)+4x-6x(do kwadratu)-9x+3=-8x(do sześcianu-12x(do kwadratu) -5x+3
e) 6=9x-2x-3x(do kwadratu)-(6-11x-10x(do kwadratu))= 6+9x-2x-3x(do kwadratu) -6+11x+10x(do kwadratu)= 18x+7x(do kwadratu)
(do kwadratu) - dopisujesz małą 2 w prawym górnym rogu x
(do sześcianu) - dopisujesz małą 3 w prawym górnym rogu x
Odpowiedź:
a) -5(3a + b - 2c)
-5 x 3a - 5b - 5 x (-2c)
Odp: -15a - 5b + 10c
b) 2(x – 3y) – 3(x – y) – 5(4x +3y)
2x - 6y - 3x +3y - 20x - 15y
Odp: -21x - 18y
c) (4 – 2x)(6x - 8)
4 x 6x - 4 x 8 - 2x x 6x - 2x x (-8)
24x - 32 - 12x^2 + 16x
40x - 32 - 12x^2
Odp: -12x^2 + 40x - 32
d) (4x + 3)(-2x² - 3x + 1)
4x x (-2x^2 - 3x + 1) + 3(-2x^2 - 3x + 1)
-8x^3 - 12x^2 + 4x - 6x^2 - 9x + 3
Odp: -8x^3 - 18x^2 - 5x + 3
e) (3 - x)(2 + 3x) – (2 – 5x)(3 + 2x)
6 + 9x - 2x -3x^2 - (6 + 4x - 15x -10x^2)
6 + 9x - 2x - 3x^2 - (6 - 11x - 10x^2)
6 + 9x - 2x - 3x^2 - 6 + 11x + 10x^2
Odp: 18x + 7x^2
Szczegółowe wyjaśnienie:
nie ma za co